Preparing Pre-Service Educators to Teach Worldview-Threatening Curriculum - van Kessel, Cathryn; Jacobs, Nick; Catena, Francesca; Edmondson, Kimberly (Journal of the Canadian Association for Curriculum Studies, 2020)
Emotions are central to teaching potentially polarizing content. This study asked pre-service teachers to engage with ideas from Ernest Becker (1973, 1975) and terror management theory (TMT) from experimental social psychology about defensive responses. In group training sessions before their teaching practicum and focus groups after their practicum, pre-service teachers considered the following questions: How might we prevent ourselves, as teachers, from treating a student harshly (or with dismissiveness) when their worldview clashes with ours? What might we need to do with our classes before worldview threatening lessons begin in order to mitigate defensive compensatory reactions? Participants explored how to facilitate contentious and potentially polarizing content and discussions so as to prevent unhelpful, defensive reactions by both students and teachers. This content included derogating people or concepts, coaxing or coercing others to your view, expressing views related to eliminating different worldviews, as well as appropriating aspects of other worldviews. A dramaturgical analysis identified participant objectives, conflicts, tactics, attitudes, emotions and subtexts. Participants explored how to anticipate and avoid worldview threat and self-esteem threat, navigate tense pedagogical spaces, build capacity for expressing uncomfortable emotions and diffuse threat with (appropriate) humour. Through their experiences, these pre-service teachers also increased their own emotional awareness. For participants, TMT became both an attitude and a teachable theory. The authors hope that both direct and indirect uses of TMT in educational contexts can help nourish less fraught social relations, helping us (as educators and humans) gain perspective on our beliefs and those of others without devaluing emotional responses.